2002
DOI: 10.1037/1076-8998.7.3.242
|View full text |Cite
|
Sign up to set email alerts
|

No security: A meta-analysis and review of job insecurity and its consequences.

Abstract: Meta-analytic techniques were used to estimate how job insecurity relates to its postulated outcomes. Consistent with the conceptual framework, the results indicate that job insecurity has detrimental consequences for employees' job attitudes, organizational attitudes, health, and, to some extent, their behavioral relationship with the organization. Moderator analyses suggest that these relationships may be underestimated in studies relying on single-item measures of job insecurity and that the behavioral cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

110
1,728
10
87

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,537 publications
(1,935 citation statements)
references
References 134 publications
110
1,728
10
87
Order By: Relevance
“…This inference is consistent with the metaanalytic finding of a negative association between job insecurity perceptions and organizational commitment (Cheng & Chan, 2008;Sverke, Hellgren, & Näswall, 2002), which is negatively related to turnover (e.g., see Griffeth, Hom, & Gaertner (2000) for meta-analytic support), as well as a positive association between job insecurity and emotional exhaustion (Boswell, OlsonBuchanan, & Harris, 2014), which is positively tied to turnover behavior (e.g., Lapointe, Vandenberghe, & Panaccio, 2011). Moreover, meta-analyses report strong evidence that perceived job insecurity and turnover intent are positively related (Cheng & Chan, 2008;Sverke et al, 2002), further suggesting that a layoff history makes one more likely to quit.…”
Section: Trust In Post-layoff Jobssupporting
confidence: 90%
See 1 more Smart Citation
“…This inference is consistent with the metaanalytic finding of a negative association between job insecurity perceptions and organizational commitment (Cheng & Chan, 2008;Sverke, Hellgren, & Näswall, 2002), which is negatively related to turnover (e.g., see Griffeth, Hom, & Gaertner (2000) for meta-analytic support), as well as a positive association between job insecurity and emotional exhaustion (Boswell, OlsonBuchanan, & Harris, 2014), which is positively tied to turnover behavior (e.g., Lapointe, Vandenberghe, & Panaccio, 2011). Moreover, meta-analyses report strong evidence that perceived job insecurity and turnover intent are positively related (Cheng & Chan, 2008;Sverke et al, 2002), further suggesting that a layoff history makes one more likely to quit.…”
Section: Trust In Post-layoff Jobssupporting
confidence: 90%
“…This inference is consistent with the metaanalytic finding of a negative association between job insecurity perceptions and organizational commitment (Cheng & Chan, 2008;Sverke, Hellgren, & Näswall, 2002), which is negatively related to turnover (e.g., see Griffeth, Hom, & Gaertner (2000) over into subsequent employment, yielding an untethering from the job, as characterized by adapted employment schema and reduced felt obligation, enhanced awareness of external job opportunities, lower trust, and heightened perceptions of job insecurity. Thus, given that these factors serve to increase the ease in and attractiveness of quitting, we expect a greater probability of voluntary turnover in jobs that follow a layoff.…”
Section: Trust In Post-layoff Jobssupporting
confidence: 88%
“…Organizational responses to the growing demand for flexibility are: increasing numbers of temporary employees with reduced job security, divided work schedules, [9,10] and incorporation of work tasks that are perceived as illegitimate [11] , e.g. professionals having to take over administrative tasks which other occupational groups could do better .…”
Section: Work-related Predictors Of Common Mental Disordersmentioning
confidence: 99%
“…Although individuals face a wide variety of potential hazards, much of this research has focused on the effects of labor market insecurity. Early works by Sverke, Hellgren andNäswall (2002), De Witte (1999), Ferrie et al (1998), McDonough (2000), Böckerman, Ilmakunnas and Johhansson (2011) and Cheng, Chen, Chen and Chiang (2005) (and many others) have shown that job insecurity is robustly linked to diminished health and wellbeing. More recent studies have expanded this thesis by (i) examining specific aspects of the insecurity/health nexus, and (ii) by employing sophisticated statistical techniques to disentangle causes from effects.…”
Section: Introductionmentioning
confidence: 99%